Search for shape coexistence in the Selenium isotopes near the N=50 neutron shell closure - Ciconali G.; Conca F.; Bottoni S.; Leoni S.; Fornal B.; Sferrazza M.; Michelagnoli C.; Mărginean N.; Corbari G.; Luciani M.; Colombi G.; Crespi F.; et al. (EPJ Web of Conferences, 2025)
Aim of this contribution is the investigation of the shape coexistence phenomenon in the neutron-rich Selenium (Z=34) isotopes at or near the N=50 shell closure, by γ-ray spectroscopy. The 83Se (N=49) and 84Se (N=50) nuclei were populated by neutron capture (ILL) and a sub-Coulomb barrier transfer reaction (IFIN-HH), respectively. The decay schemes of both nuclei were significantly extended and they are still under investigation. Concerning the 83Se, γ-spectroscopy data allowed for the identification of 28 new primary γ transitions, 16 new levels and 89 new secondary γ transitions. Firm spin and parity assignment of the newly found states will be obtained from angular correlation investigation, currently ongoing. In the case of 84Se, the γ decay from the second and third 0! states were observed for the first time and preliminary results from lifetime measurements were obtained for both the states.